Extração supercrítica do cardanol a partir do líquido da casca da castanha de caju e sua incorporação em matriz de PLGA : modelagem matemática e avaliação da atividade citotóxica - Ferreira, Cristina Lorenski (2022)
Cashew nut shell liquid (CNSL) is an agroindustrial by-product that has peculiar characteristics due to its rich composition of alkylphenols. Among its phenolic constituents, cardanol stands out, which has attracted attention for having an antiproliferative effect on cancer cells. The objective of this work is to study the supercritical CO2 extraction (SFE) process of cardanol from the technical CNSL and to produce biodegradable PLGA films with incorporated cardanol for potential application in the therapy of bladder cancer (T24) and glioblastoma (M059J). Experimental conditions were investigated for the extraction of cardanol from CNSL. The Box Behnken method was used to optimize cardanol yield as a function of pressure, temperature and solvent flow variables. Vapor-liquid equilibria experiments (VLE) were conducted to determine the solubility of cardanol in CO2. The VLE experimental data were modeled using the PR-EOS coupled to the van der Waals mixing rule (vdW2) and the SFE process was simulated using a model proposed by Sovová (2005). The extracts were characterized by FTIR, 1H NMR, HPLC, GC/MS and the cytotoxic activity was evaluated for T24 and M059J cells. PLGA films with cardanol were prepared with the solvent evaporation method and characterized; release assays were performed and mathematical modeling of the kinetics determined. As a result, extracts with 94% of cardanol with activity against T24 and M059J cells (IC50 of 21.5 and 86.6 μg/mL, respectively) stand out. By the Box-Behnken method, the greatest influence of pressure on cardanol yield was observed. In the condition of 50 °C/150 bar, the solubility was calculated as 0.087gcard./kgCO2. In this study, SFE proved to be technically viable for obtaining cardanol from CNSL and PLGA films with cardanol showed adequate properties with potential to be applied in the treatment of bladder cancer and glioblastoma.